Impact of green finance on China’s high-quality economic development, environmental pollution, and energy consumption - Li, Chenggang; Chen, Ziling; Wu, Yiping; Zuo, Xintong; Jin, Han; Xu, Yunbao; Zeng, Bingying; Zhao, Gang; Wan, Yikang (Frontiers in Environmental Science, 2022)
Green finance is an important practice of China’s high-quality economic development in the new era, which is closely related to economic development, environment and energy conditions. However, few studies systematically analyze the impact of green finance on economic development, environmental pollution and energy consumption, especially on China which is turning to high-quality economic development. In order to fill the gap, based on the annual data of 30 provinces (autonomous regions and municipalities) in China from 2008 to 2018, we construct a comparatively comprehensive green finance index system and use panel regression model to explore the impacts of green finance on high-quality economic development, environmental pollution and energy consumption. We find that green finance can significantly promote high-quality economic development, mitigate environmental pollution and reduce energy consumption. There is spatial and temporal heterogeneity of the impact of green finance on China’s economic quality, environmental pollution and energy consumption. In the eastern region, green finance has a remarkable positive impact on high-quality economic development and a significant negative impact on energy consumption, but the impact on environmental pollution is inconspicuous. In the central region, green finance has a prominent effect on reducing environmental pollution, but the impact on high-quality economic development and energy consumption is not significant. In the western region, green finance has not been able to significantly promote high-quality economic development, mitigate environmental pollution and reduce energy consumption. After the clear proposal of green finance, the role of green finance in promoting high-quality economy has enhanced, and the role of green finance in reducing environmental pollution and energy consumption has decreased. This study can provide useful decision-making reference for promoting high-quality economic development, reducing environmental pollution and energy consumption and spurring sustainable development.